Analysis of the morbidity characteristics and related factors of pulmonary nodules in patients with type 2 diabetes mellitus: a retrospective study - Jie Yang; Wenna Wang; Yizhen Lu; Chunyao Li; Shuwu Wei; Weiwei Sun (BMC Endocrine Disorders)
Abstract Objective To analyze the characteristics of pulmonary nodules (PNs) and related influencing factors in patients with type 2 diabetes mellitus (T2DM). Methods Retrospectively analyzed the clinical and biochemical characteristics of 224 patients with PNs and 488 patients with non-PNs in patients with T2DM, and compared the clinical data of 72 patients with large nodules (≥ 5 mm) and 152 patients with small nodules (< 5 mm) in the pulmonary nodules (PNs) group. Results Compared to the non-PNs group, the PNs Patients in the group had a longer duration of diabetes, higher age, serum creatinine (SCR), blood urea nitrogen (BUN) and the lower albumin (ALB) and body mass index (BMI); women, diabetic retinopathy (DR), diabetic peripheral neuropathy (DPN), and estimated glomerular filtration rate (eGFR) < 60 ml/min1.73m2 were more represented in the PNs group; there were fewer patients with overweight in the PNs group. Age and eGFR < 60 ml/min/1.73m2 were independent risk factors for PNs in patients with T2DM, and overweight was associated with a reduced risk of PNs. Compared with the small nodule group, patients in the large nodule group had higher fasting blood glucose (FBG) and lower fasting insulin (FINS); meanwhile, patients with decreased homeostasis model assessment-β (HOMA-β) and high smoking index (SI) were higher in the large nodule group; decreased HOMA-β and high SI were independent risk factors for large nodules. Conclusions Age and eGFR < 60 ml/min/1.73m2 were independent risk factors for pulmonary nodules in patients with T2DM, and overweight may be a protective factor. Moreover, decreased islet B-cell function and smoking may contribute to the presence of PNs with a diameter of over 5 mm.